Tel1/ETV6 specifies blood stem cells through the agency of VEGF signaling. - Ciau-Uitz, A; Pinheiro, P; Gupta, R; Enver, T; Patient, R (2010)
The regulation of stem cell ontogeny is poorly understood. We show that the leukemia-associated Ets transcription factor, Tel1/ETV6, specifies the first hematopoietic stem cells (HSCs) in the dorsal aorta (DA). In contrast, Tel1/ETV6 has little effect on embryonic blood formation, further distinguishing the programming of the long- and short-term blood populations. Consistent with the notion of concordance of arterial and HSC programs, we show that Tel1/ETV6 is also required for the specification of the DA as an artery. We further show that Tel1/ETV6 acts by regulating the transcription of VegfA in both the lateral plate mesoderm and also in the somites. Exogenous VEGFA rescues Tel1/ETV6 morphants, and depletion of VEGFA or its receptor, Flk1, largely phenocopies Tel1/ETV6 depletion. Few such links between intrinsic and extrinsic programming of stem cells have been reported previously. Our data place Tel1/ETV6 at the apex of the genetic regulatory cascade leading to HSC production.